PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF POWERPOINT BERBASIS INKUIRI TERBIMBING PADA MATERI ZAT ADITIF KELAS VIII SMP/MTS - Alizar, Anggun Oktafi Hanif, Syamsi Aini (Menara Ilmu, 2019)
Additive Substance is the science subject matter for grade VIII SMP in semester one.This material is closely related to daily life. To understand this material we need a mediathat are suitable with curriculum 2013. One of media that can be used is powerpointinteractive learning media based on guided inquiry. The purpose of this research was todevelop powerpoint interactive learning media based on guided inquiry on additivematerial and showed the validity and practicality. This research was development researchwith 4-D model (define, design, develop, and disseminate). This research was limited to thedevelop stage, which is testing the validity and practicality of the media. The instrument ofthis research was validity and practicality questionnaire. The media developed wasvalidated by 5 validators, they are 3 chemistry lecturers and 2 science teachers. Thepracticality questionnaire was filled by 2 natural science teachers and 31 students in gradeIX 1 at SMPN 3 Payakumbuh. Data from the validity and practicality results wereanalyzed using the Cohen Kappa formula. From the results of the validity, the average ofkappa moment was 0.82 with a very high validity category. From the results of thepracticality on the teacher, the average of kappa moment was 0.88 and on the studentswere 0.87 with a very high practicality category. Based on the results of the study, it canbe concluded that the developed inquiry-based additive-based learning media is valid andpractical.Keyword : Interactive, Powerpoint, Guided Inquiry, Additive Substances